New Book for Elementary and Middle Grades Highlights Ocean Literacy Principle 6. Issue 1 (1st November 2021) - Christopher, David
Using stunning photography and real stories of people and groups working in ocean conservation, Planet Ocean: Why We All Need a Healthy Ocean inspires young readers to help spread conservation messages and take action to help the ocean.